2018
DOI: 10.1002/solr.201800144
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Double Buffer Layer Sb2 (SexS1–x)3 Thin Film Solar Cell Via Single Source Evaporation

Abstract: Sb2(SexS1–x)3 has been proven a very promising light absorbing material for photovoltaic applications due to its high stability, tunable band gap, non‐toxic element, and high extinction coefficient. For Sb2(SexS1–x)3 alloy film deposition, the authors develop a single source based rapid‐thermal‐evaporation (RTE) method instead of the traditional in‐situ sulfurization or double source co‐evaporation based RTE method. The absorber band gap can be precisely tuned from 1.1 to 1.7 eV by simply varying the molar rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 88 publications
(54 citation statements)
references
References 30 publications
1
50
0
Order By: Relevance
“…The series resistance (R) can be obtained by extrapolating the plots of dJ/dV against (J+J SC ) -1 to the Y-axis while the diode ideality factor (A) can be calculated as the slope of AkT/q (Figure 5c). [42] The series resistance and diode ideality factor were calculated to be R = 8.03 Ω/cm 2 configuration. [40,[43][44][45] It has been reported that such an interfacial layer between the absorber layer and Mo substrate with appropriate thickness could decrease the back contact barrier to improve the carrier transport and reduce the recombination loss.…”
Section: Resultsmentioning
confidence: 99%
“…The series resistance (R) can be obtained by extrapolating the plots of dJ/dV against (J+J SC ) -1 to the Y-axis while the diode ideality factor (A) can be calculated as the slope of AkT/q (Figure 5c). [42] The series resistance and diode ideality factor were calculated to be R = 8.03 Ω/cm 2 configuration. [40,[43][44][45] It has been reported that such an interfacial layer between the absorber layer and Mo substrate with appropriate thickness could decrease the back contact barrier to improve the carrier transport and reduce the recombination loss.…”
Section: Resultsmentioning
confidence: 99%
“…[22,33] To understand the nature of dopant and its effect on Sb 2 S 3 energy levels, ultraviolet photoelectron spectroscopy (UPS) was conducted to investigate the energy level evolution. [23] The UPS spectra of Sb 2 S 3 and Cu-Sb 2 S 3 are shown in Figure 4a Figure 4c. These results demonstrated that our doped material was p-type and obtained a small up-shift in valance band (E v ).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we established a coevaporation method from Sb 2 S 3 and CuS mixture source to efficiently dope Sb 2 S 3 with copper via our previous RTE-based thin-film technique. [23] Using single-step deposition method, the fabricated films exhibited vertically oriented ribbons and large grains, which helped to reduce the recombination defects, whereas the other random orientations were significantly suppressed. The Cu doping can also reduce the resistivity and defect concentration, enhance carrier concentration, and balance the band offset between Sb 2 S 3 and Au, which profoundly improves J sc from 14.6 to 15.2 mA cm À2 and FF from 45.8% to 47.6%.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, using CdS as an ETL would slant to a sacrifice of short light absorption leading to a lower current density ( J SC ). [16] Recently, the encouraging results of Cd-free buffer layers such as SnO 2, [17] ZnO, [18] and TiO 2 [19] pave further research to overcome this inadequacy, where TiO 2 as ETL has been well-intentioned by promoting the epitaxial growth mechanism for Sb 2 S 3 films. [4] In the last decade, frequent cutting-edge investigations have advanced the TiO 2 /Sb 2 S 3 interface properties by doping in TiO 2 and its surface treatment.…”
Section: Introductionmentioning
confidence: 99%